Effects of nitridation temperature on properties of sintered reaction‐bonded silicon nitride. Issue 2 (17th August 2022) - Nakashima, Yuki; Zhou, You; Tanabe, Keisuke; Arima, Souhei; Hirao, Kiyoshi; Ohji, Tatsuki; Fukushima, Manabu
Abstract: We prepared sintered reaction‐bonded silicon nitride ceramics by using yttria and magnesia as sintering additives and evaluated effects of the nitridation temperature on their microstructure, bending strength, fracture toughness, and thermal conductivity. The effects of the nitridation temperature were large, but different depending on the property. The ratio of β‐phase in the nitrided compacts significantly increased with increasing the nitridation temperature, whereas their microstructures had no clear difference. Although the bending strength varied, it maintains a high value of 800 MPa. Fracture toughness was almost constant regardless the temperature. The thermal conductivity improved as the β‐phase in the nitrided compact increases. This resulted in a decrease of the lattice oxygen content and increase of the thermal conductivity. Therefore, elevating the nitridation temperature and consequently the β‐phase ratio should be a promising strategy for achieving compatibly high strength and high thermal conductivity, which are generally known to be in a trade‐off relationship.